Measuring technical efficiency of Ethiopian commercial banks: multiple criterion data envelopment analysis - Alem Gebremedhin Berhe (Cogent Business & Management)
This study attempts to measure the technical efficiency of Ethiopian commercial banks and explore its determinants in the growth and transformation plans (GTP I, 2011–2015 and GTP II, 2016–2020). It uses a two-stage analysis based on balanced panel data during 2011–2020 for 18 commercial banks in the Ethiopian context. First, the data envelopment analysis (DEA) approach was used to estimate the technical efficiency (TE) of the banks that were the subject of the research. The second step, on the other hand, uses the Tobit regression model to regress all independent variables (both macroeconomic and bank-specific) on the technical efficiency (TE) of the banks that are being studied. The results of the Tobit regression also show that bank TE is positively and significantly correlated with staff productivity, off-balance sheet activities, capitalization level, GDP (gross domestic product) growth, and inflation. However, throughout the GTP II period, Ethiopian banks’ TE increased as staff productivity, off-balance sheet activities, bank size, and liquidity risk improved. This research gives bankers, regulators, policymakers, and promoters information into how viable the Ethiopian banking industry is. It suggests that merging ineffective banks will result in beneficial synergies and could act as a buffer for a developing nation such as Ethiopia.